Peran Ukuran Pemusatan Dan Letak Data Dalam Evaluasi Statistik Pendidikan Di Sekolah - Basmala Siarkanasa; Prihaten Maskhuliah; Faujiah M. Lau; Muh. Rezha Irman; Hasan Lulang (CV. ITTC INDONESIA, 2025)
Educational evaluation is not limited to descriptive assessments but requires the application of a structured statistical approach to obtain an objective picture of learning achievement. Measures of central tendency (mean, median, mode) and measures of position (quartiles, deciles, percentiles) play a vital role in mapping students’ score distributions, identifying disparities, and supporting data-driven decision-making. Based on a review of the literature and relevant regulations, including Ministry of Education and Culture Regulation No. 23 of 2016, transparent and accountable evaluation requires the integration of these two types of measures. This study employs a literature review method by examining books, scholarly journals, and official documents. The findings reveal that measures of central tendency provide a summary of the middle value, while measures of position indicate the relative standing of scores within the distribution. Together, they can be used to detect outliers and design more targeted learning interventions. A simulation using hypothetical data demonstrates that applying these measures yields a more accurate categorization of achievements compared to relying solely on the average. In decision-making, the application of both classical and Bayesian statistical methods can improve the accuracy of planning, control, and prediction of learning outcomes. This study underscores that mastering and optimally applying measures of central tendency and position constitutes a strategic step in enhancing the quality of learning evaluation in schools. (Gelman et al., 2013